Evaluating the role of verbal behavior on “superstitious” behavior acquisition (Revista Brasileira de Terapia Comportamental e Cognitiva, 2007)
The experiment evaluated interactions between instructions and behavior acquired by accidental relations with reinforcement (“superstitious” behavior). Four adults participated on a computer task. In each session there were 30 s periods in which the participants could respond by clicking with a mouse upon a colored rectangle displayed on the screen. At the end of each 30 s period, there was one interval of 10 s in which the participant could ask to quit. Four individual sessions were used, and in each of them there was only one contingency for scoring points: VR 6, extinction, extinction and VT 8 s. At the beginning of the last two sessions, the participants were told that no responses to the rectangle scored points. Three participants responded more in the last session than in the third, showing that instructions implying relationship between response and environmental change can facilitate the acquisition of “superstitious” behavior.
Keywords: “Superstitious” behavior; Computer; Verbal